Acute visceral cysticercosis by Taenia hydatigena in lambs and treatment with praziquantel. Issue 1 (14th August 2014) - Scala, A.; Urrai, G.; Varcasia, A.; Nicolussi, P.; Mulas, M.; Goddi, L.; Pipia, A.P.; Sanna, G.; Genchi, M.; Bandino, E.
Abstract: An acute outbreak of Taenia hydatigena cysticercosis, causing mortality in 5 of 21 (23.8%) female lambs, is reported. Gross post-mortem examinations and histology showed Cysticercus tenuicollis as the cause of death. Biochemical parameters in infected lambs confirmed severe hepatitis. Praziquantel, given once at 15 mg/kg body weight (bw), was administered and a dramatic improvement in the clinical condition and biochemical parameters was observed up to 30 days following treatment.